Urbanisation Drives the Decoupling, Simplification, and Homogenization of Aquatic and Terrestrial Food Webs - Kilian Perrelet; Lauren M. Cook; Merin Reji Chacko; Florian Altermatt; Marco Moretti (Ecology Letters, 2025)
Aquatic and terrestrial communities often co‐occur at close distances, enabling biotic interactions across ecosystem boundaries. While such interactions in natural habitats contribute to complex, coupled food webs, their dynamics in engineered and fragmented urban habitats are hardly known. Using environmental DNA metabarcoding and a metaweb approach, we examined food web structure at 54 paired aquatic‐terrestrial sites along an urbanisation gradient in Zurich, Switzerland. We found that urbanisation led to simpler, less connected, and more homogeneous food webs by replacing high‐trophic‐level predators with low‐trophic‐level basal consumers. This shift towards basal consumers, dependent on distinct aquatic or terrestrial basal resources, subsequently weakened the links between aquatic and terrestrial food webs. Conversely, enhancing habitat quantity and landscape connectivity bolstered predator diversity, promoting vertically diverse, connected, complex, and stable food webs. Our findings reveal that while urbanisation can disrupt aquatic‐terrestrial food webs, careful urban habitat planning can enhance biodiversity and food web stability.